1987
DOI: 10.1136/oem.44.8.559
|View full text |Cite
|
Sign up to set email alerts
|

Mortality due to respiratory cancers in the coke oven plants of the Lorraine coalmining industry (Houilleres du Bassin de Lorraine).

Abstract: The main activity of the Houilleres du Bassin de Lorraine (Lorraine Collieries), employing 23 000 operatives and executives, is coalmining. The coke production is carried out by two coke oven plants with a workforce of respectively 747 and 552 workers. The coal coking process entails the emission of noxious products such as polycyclic aromatic hydrocarbons (PAH) from the ovens. The influence of occupational exposure on mortality due to respiratory cancers, and particularly to lung and upper respiratory and ali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Environmental Protection Agency (USEPA) (USE-PA, 2006) and the International Agency for Research on Cancer (IARC, 2004). Epidemiological studies on populations exposed to PAH mixtures have shown a link between these exposures, and cancers of the lung, respiratory system, and stomach (Bertrand et al, 1987;Puisieux et al, 1991;Krewski and Thomas, 1992;Vyskocil et al, 2004). Smoking and exposure to environmental tobacco smoke (ETS) have been shown to be associated with cancer in the lung, bronchus, larynx, bladder, cervix, and oral mucosa (Phillips, 1997;Lee et al, 2006;Yach and Wipfli, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental Protection Agency (USEPA) (USE-PA, 2006) and the International Agency for Research on Cancer (IARC, 2004). Epidemiological studies on populations exposed to PAH mixtures have shown a link between these exposures, and cancers of the lung, respiratory system, and stomach (Bertrand et al, 1987;Puisieux et al, 1991;Krewski and Thomas, 1992;Vyskocil et al, 2004). Smoking and exposure to environmental tobacco smoke (ETS) have been shown to be associated with cancer in the lung, bronchus, larynx, bladder, cervix, and oral mucosa (Phillips, 1997;Lee et al, 2006;Yach and Wipfli, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The contaminants emitted during coking include inorganic compounds, heavy metals, OC, and EC (Tsai et al, 2007;Mu et al, 2012;Liu et al, 2013;Mu et al, 2013;Liu et al, 2014). Coke-plant workers are exposed to organic pollutants, leading to high lung cancer mortality (Redmond, 1983;Bertrand et al, 1987). In China's Shanxi province, OC and EC emissions from coking are second only to domestic coal emission and are much higher than those from biomass combustion, power plant and vehicle emissions (Cao et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that boilermakers are exposed to PAH and metals during the workweek, as indicated by repeated urinary sampling and measurement of 1-OHP and individual metal biomarkers of exposure. This is important because workers exposed to high levels of PAH, such as coke oven and aluminum industry workers, demonstrate an increased risk of cancer [IARC, 1983[IARC, , 1984[IARC, , 1985Bertrand et al, 1987;Verma et al, 1992]. Similarly, the carcinogenic potential of nickel and chromium has been well established for humans and experimental animals [IARC, 1990;Man, 1990;Hayes, 1997;Merzenich et al, 2001].…”
Section: Discussion Boilermakers Are Exposed To Metals and Pahmentioning
confidence: 96%